Blogging: an emerging innitiative amongst librarians in Oyo State Nigeria (2015)
This paper examines blogging as an emerging initiative among librarians in Nigeria. It looks at how librarians having embraced the blogging technology have used it not only to promote themselves but to also promote the activities of their affiliate organizations. The attitude of librarians to ownership and operation of weblogs was also examined. It aims at investigating Librarians’ awareness of weblogs, their attitudes to weblog and the benefits accruable to the individual and the library in weblog operations. The descriptive survey research method was used with questionnaire questions drawn up in line with the objectives of the study. A hundred questionnaires were distributed to Librarians in Oyo State, Nigeria out of which ninety eight were returned. Data gathered was analyzed using the frequency count and simple percentages. Conclusions were then drawn from the analyzed data and recommendations made on how librarians can and should exploit the benefits of weblogs and blogging to advance librarianship.